Modeling and dynamic analysis of wind turbines - Cosico, Roochie Mico V.; Tan, Liezl Raissa E.; Hernandez, Jaime Y. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The structural response of a 2 kW horizontal axis wind turbine subjected to wind loads is simulated. The support structure is a land-based 20 m high steel tower with guy wires. A dynamic analysis is performed using Computational Fluid Dynamics (CFD) to estimate wind loads and Finite Element Method (FEM) modeling to determine the response, i.e., stresses and deformations. Factors of safety are also calculated to determine the strength adequacy of the structure. The fluid flow and structural analyses are coupled using the concept of Fluid-Structure Interaction (FSI). Three loading conditions, namely, operational, extreme wind and failure, are used for the analysis. The blades are rotating at 400 rpm in operational and failure condition, while they are parked in extreme condition. FSI is incorporated in the tower only during operational and failure conditions. Wind loads on the blades are simplified as equivalent concentrated forces. On the other hand, in extreme condition, FSI is used for the whole structure. RANS equations with Shear Stress Transport k - ω turbulence model are used in the CFO component. The study shows that the structure is adequately designed, with a minimum factor of safety of 2.9 for operational and extreme conditions. The yaw pipe is the critical area and may require further design considerations. Majority of the stress comes from the weights of the parts it supports. Stresses in the blades are found to be lower in extreme condition. The main reason is that wind load acting on fast-rotating objects is far greater than that experienced by a stationary object. Wind condition at the onset of failure is also investigated. By trial, the minimum operational wind speed at which failure occurs is obtained. At this failure condition, the yaw pipe fails. Fundamental modal frequencies of the structure are also output to check whether resonance is likely to occur.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Horizontal axis wind turbines -- Design and construction; Wind turbines